Considerations on an Indicator Guaranteed in the Electricity Supply to Consumers. (2015) - Hazi, Gheorghe; Bică, Dorin; Hazi, Aneta
Abstract: An important indicator in assessing the quality of the network connection solutions for electricity consumers is the maximum time it takes to restore power after interruptions. The calculation methodology which is presented in the specialized technical prescriptions runs into practical difficulties as the probability of defect removed by repair is very low. The maximum value of the restoration time is based on the mean reliability indicators of the supply network. In this paper, the authors establish a relationship for computing the maximum restoration time and propose applications for it in cases where the method presented in the normative can lead to erroneous results. In the determined relationship the Poisson distribution is applied, ie the law of rare events.